THE REMAINS OF THE LETTERS. THREE READING PARADIGMS IN THE GHETTOS - Roszak, Joanna (Porównania, 2018)
In June 1942 Emanuel Ringelblum asked: “What kind of books do people read? This topic has always been interesting for each Jew and after the war it also became interesting to the world”. This topic hasn’t received a comprehensive study yet. The author of the paper The Remains of the Letters. Three Reading Paradigms in the Ghettos examined this aspect of history of the ghettos. The literature allows us to shed light on the topic of the life and deaths of their inhabitants. But, taking up this topic enables us also to activate new ways of interpreting the books. The volumes they spent time on in the ghetto allow to capture the way the residents of the ghettos built or broke the bond with the reality, how they taught their own children to read or found solace in someone else’s pain. The author considers, however, whether the studies of ordinary life in extraordinary times of the Holocaust can be considered micro-historical.